2017
DOI: 10.1007/s00244-016-0361-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Strategy, Sediment Characteristics, and Chemical Properties on Polychlorinated Biphenyl and Polybrominated Diphenyl Ether Bioaccumulation from Marine Sediments in Two Invertebrates

Abstract: Shellfish and sediment invertebrates have been widely used to assess pollution trends over space and time in coastal environments around the world. However, few studies have compared the bioaccumulation potential of different test species over a range of sediment-contaminant concentrations and profiles. The bioavailability of sediment-related contaminants was evaluated using sediments collected from sites (n = 12) throughout the Salish Sea, British Columbia, Canada. Two benthic marine invertebrates-the Baltic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Concentrations of PBDEs in limpets were significantly higher (Figure ) than those in sea cucumbers, ascidians, and sea stars, while the differences between sea urchins and all the other species were not significant, possibly due to the low number of samples ( n = 3). This is different from the trends seen for PCBs (Figure ), which, however, is in close agreement with recent experimental work on accumulation patterns of PCBs and PBDEs in invertebrates with different feeding behaviors, which showed that concentrations of PCBs tended to increase more rapidly than that of PBDEs with increasing trophic level …”
Section: Resultssupporting
confidence: 79%
“…Concentrations of PBDEs in limpets were significantly higher (Figure ) than those in sea cucumbers, ascidians, and sea stars, while the differences between sea urchins and all the other species were not significant, possibly due to the low number of samples ( n = 3). This is different from the trends seen for PCBs (Figure ), which, however, is in close agreement with recent experimental work on accumulation patterns of PCBs and PBDEs in invertebrates with different feeding behaviors, which showed that concentrations of PCBs tended to increase more rapidly than that of PBDEs with increasing trophic level …”
Section: Resultssupporting
confidence: 79%